Determination of Antifungal and Anti-Aflatoxigenic Activity of the Essential Oil of Lippia lasiocalycina Cham (Verbenacea) - Wanessa Sales de Almeida; Sidney Gonçalo de Lima; Marcelo Costa dos Santos; Cândido Athayde Sobrinho; Rafael Gomes Abreu Bacelar; Maria Christina Sanches Muratori (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Contamination of food by aflatoxin-producing fungal species generates huge economic losses and directly affects the health of consumers. The search for more natural preservation methods has raised interest in the potential of essential oils like antifungals in food. In this study, we aimed to evaluate the potential inhibition of Lippia lasiocalycina essential oil on fungal growth and aflatoxin B1 production by Aspergillus flavus strains. The minimum inhibitory concentration of the essential oil of L. lasiocalycina was determined against a strain of Aspergillus flavus. The potential for inhibition of fungal growth and aflatoxin B1 production was tested by direct contact and by the action of volatile compounds. Aflatoxin production was determined by HPLC. L. lasiocalycina essential oil inhibited 94% growth of Aspergillus flavus by direct contact and the volatile compounds potentiate the production of aflatoxin B1. The essential oil of Lippia lasiocalycina proved to be applicable in the production chain of aflatoxin B1 marketed as standard for use in scientific research.